Biomimetic bone-like apatite coating on anodised titanium in simulated body fluid under UV irradiation - Lee, T.C.; Koshy, P.; Abdullah, H.Z.; Idris, M.I. (Trans Tech Publications, 2017)
Low temperature deposition techniques of bioceramics coatings are now being researched and developed to avoid deficiencies inherent in high temperature techniques. Biomimetic coatings are a solution-based method conducted at ambient temperature to deposit bioactive coatings on the surface. The current study aims to investigate the effect of ultraviolet (UV) irradiation on the coating of bone-like apatite on the anodised surface. High purity titanium foils were anodised with an applied voltage of 350 V, current density of 70 mA.cm-2 in mixture of 0.04 M β-glycerophosphate disodium salt pentahydrate (β-GP) and 0.4 M calcium acetate (CA) for 10 min. After anodic oxidation, UV light treatment was conducted in pH-adjusted distilled water for 12 h with ultraviolet light A (UVA) irradiation. Subsequently, the UV-treated anodised titanium foils were soaked in SBF for 7 days with/without UVA irradiation. After SBF immersion for 7 days, anodised titanium with combination of UV light treatment and UV irradiation during in vitro testing was fully covered by highly crystalline bone-like apatite at maximal thickness of 2.8 μm. This occurred mainly due to the formation of large amounts of Ti-OH groups which act as nucleation sites for bone-like apatite. This study also revealed that UV irradiation during in vitro testing is superior in promoting growth of bone-like apatite compared to UV light treatment. The suggested mechanism for bone-like apatite formation on anodised titanium under different UV irradiation conditions is illustrated in this article. The findings of this study indicated that biomimetic bone-like apatite coating with assistance of UV irradiation is an effective method in accelerating the formation of bone-like apatite.